Specific Frequency Electroacupuncture Stimulation Transiently Enhances the Permeability of the Blood-Brain Barrier and Induces Tight Junction Changes - Zhang, Shanshan; Gong, Peng; Zhang, Jiangsong; Mao, Xuqing; Zhao, Yibin; Wang, Hao; Gan, Lin; Lin, Xianming (Frontiers in Neuroscience, 2020)
The blood-brain barrier (BBB) plays an important role in both the physiological state and pharmacological state of the brain. Transiently enhancing the permeability of the BBB may allow the use of more types of medications for neuropsychiatric diseases. Our previous research revealed that electroacupuncture (EA) stimulation at certain parameters can enhance the permeability of the BBB in Sprague-Dawley rats, but this phenomenon is not well characterized. We propose that specific frequency electroacupuncture can transiently open the BBB and may be related to the change of tight junctions (TJ). To find the best EA frequency among commonly used frequencies, preliminarily explore the mechanism, we detected BBB permeability by measuring the intensity of Evans Blue and 20 kDa FITC-dextran fluorescence in the cerebral cortex. Then, we used a laser spectrometer, immunofluorescence, western blotting, and transmission electron microscopy to detect the mechanism of BBB opening. Finally, measured brain water content, AQP4, GFAP, Iba1, and used the DeadEndTM Fluorometric TUNEL System to clear whether the stimulation caused obvious negative effects. The results show that EA stimulation at 2/100 Hz maximally increased BBB permeability, and the BBB closed within 12 h after EA stimulation was removed. EA stimulation increased blood perfusion, c-fos levels, and Substance P expression in the cerebral cortex, decreased ZO-1 and occludin levels and induced ultrastructural changes in TJ morphology. EA stimulation at specific parameters did not cause brain edema, activation of glial cells, or cell apoptosis. This study shows that EA stimulation induces a reversible, frequency-dependent alteration of BBB permeability and proposes a hypothetical mechanism of BBB opening related to vasodilation and TJ disruption. Transiently enhancing the permeability of the BBB with EA at specific parameters may be a new strategy for delivering therapeutics to the central nervous system. Further study of this technology is needed.